Determination of percentage depth dose for 6 and 10 MV x-rays using Ge-doped optical fibre and TLD-100 - Abdulla, Y.A. (Institute of Physics, 2002)
Percentage depth doses for 6 and 10 MV x-ray beams from a linear accelerator were measured using ~1 cm long (~0.3 mg) Ge-doped optical fibre as a thermoluminescence dosimeter for two field sizes, 5 × 5 and 10 × 10 cm2. The results indicate that the Ge-doped optical fibre dosimeter is in good agreement with the results from a PTW 30001 cylindrical ionisation chamber and TLD-100. For 6 MV x-ray beams we observe that the depth of maximum dose dmax is 1.5 and 2 cm for field sizes of 5 × 5 and 10 × 10 cm2 respectively. For 10 MV dmax is 2 cm for a field size of 5 × 5 cm2 and 2.5 cm for a 10 × 10 cm2 field.